2022
DOI: 10.1523/jneurosci.0997-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Migrating Pyramidal Neurons Require DSCAM to Bypass the Border of the Developing Cortical Plate

Abstract: During mammalian neocortex development, nascent pyramidal neurons migrate along radial glial cells and overtake earlier-born neurons to terminate at the front of the developing cortical plate (CP), leading to the outward expansion of the CP border. While much has been learned about the cellular and molecular mechanisms that underlie the migration of pyramidal neurons, how migrating neurons bypass the preceding neurons at the end of migration to reach their final positions remains poorly understood. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Closer examination of gene expression differences between neurons and neuroblasts showed that genes critical for neuronal migration in the mouse were induced in the neuron class cells, including DAB1, VLDLR and DSCAM ( 16, 17 ). In contrast, genes that are uniquely expressed in the germinal zone, such as PPP17R1 and NEUROD4 were observed in neuroblasts ( 18, 19 ) (table S4).…”
Section: Excitatory Lineage Of the Developing Neocortexmentioning
confidence: 99%
“…Closer examination of gene expression differences between neurons and neuroblasts showed that genes critical for neuronal migration in the mouse were induced in the neuron class cells, including DAB1, VLDLR and DSCAM ( 16, 17 ). In contrast, genes that are uniquely expressed in the germinal zone, such as PPP17R1 and NEUROD4 were observed in neuroblasts ( 18, 19 ) (table S4).…”
Section: Excitatory Lineage Of the Developing Neocortexmentioning
confidence: 99%
“…In our recent paper, Migrating pyramidal neurons require DSCAM to bypass the border of the developing cortical plate , we described the termination process of neuron radial migration and reported a molecular mechanism that underlies this process ( Yang et al, 2022 ). We found that the nascent pyramidal neuron bypassing the last preceding neuron is important for expanding the cortex and thus determines the thickness of the upper cortical layers.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we applied live cell time-lapse imaging on organotypic brain-slice cultures to observe the termination of radial migration in detail ( Yang et al, 2022 ). Organotypic brain slice cultures preserve brain development within an ex vivo environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RG cells have the capacity for self-renewal to expand the neural progenitor cells (NPCs) pool and can differentiate into intermediate progenitor cells or neurons directly ( 2 , 3 ). The newborn neurons then migrate to their final destinations in the different layers of the cerebral cortex ( 4 , 5 ). Dysfunctions of early neurodevelopment, including neurogenesis and neural migration, have been associated with structural malformations of the human brain.…”
Section: Introductionmentioning
confidence: 99%